PEMBELAJARAN IPA FISIKA DENGAN MODEL GUIDED-DISCOVERY PADA MATERI SUHU DAN KALOR UNTUK MENINGKATKAN KETERAMPILAN PROSES SISWA KELAS VII DI SMP NEGERI 40 PEKANBARU - Rahma Juwita; Mitri Irianti; Muhammad Sahal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to describe student’s proses skill with a Guided-Discovery Model on matter of temperature and heat. Population in this study were all 7th of class in SMP Negeri 40 Pekanbaru. Sample were taken from 2 homogeneous classes, then randomly determined experimental classes that applied Guided-Discovery model and conventional classes. The type of this research is quasi experiments by the design of intact group comparison; the instrument used is a process skill test. Data collection techniques used is descriptive and inferential analysis. The results of the study state that there are differences in student process skills between the experimental class and the conventional class. Average absorption of experimental class 71,1 while the conventional class with an average of 56. Thus the implementation of Guided-Discovery model can improve process skills.Key Words: Guided-Discovery, Process Skills, Temperature and Heat